(untitled) (Medicine Today, 2021)
Introduction: Ultrasound measurements of the intima media thickness (IMT) in the carotid arteries is a strong predictor for cardiovascular events both in the general and diseased population. Materials & Methods: This cross-sectional analytic study was conducted to observe correlation of CIMT with age, body mass index (BMI) and glomerular filtration rate (GFR) in chronic kidney disease (CKD). The study was done in Department of Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, on 80 chronic kidney disease patients, from July 2014 to June 2015. All the biochemical parameters were measured according to the standard laboratory techniques. Body mass index (BMI) was calculated by person’s body weight divided by height. Glomerular filtration rate (GFR) was calculated using the modification of diet in renal disease (MDRD) formula. CIMT measurement was done by duplex study of carotid vessels through high resolution B-mode ultrasound. Results: Mean age of the patients was 36.1±9.5 years. 20 (25%), 26 (32.5%) and 34 (42.5%) patients were in CKD stage 3, 4 and 5 respectively. Age, serum creatinine and GFR showed statistically significant difference among stage 3, 4 and 5 CKD patients (p<0.001). However, no difference was evident in BMI and mean CIMT among stage 3, 4 and 5 CKD patients. Significant positive correlations were found between age and CIMT (r=+0.332; p=0.003) and BMI and CIMT (r=+0.294; p=0.008). However, no significant correlation was evident with estimated glomerular filtration rate (eGFR) and CIMT (r=–0.181; p=0.109). Conclusion: Age, serum creatinine and estimated glomerular filtration rate showed statistically significant difference among different stages of CKD patients (stage 3, 4 and 5). There were significant positive correlations found in between age and CIMT as well as BMI and CIMT in chronic kidney disease patients, with an exception to GFR and CIMT. Medicine Today 2021 Vol.33(2): 147-151